2011
DOI: 10.1021/ef200440k
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Carbon Dioxide in Hydrothermal Cracking of Polymer Wastes

Abstract: T he Earth's environment is seriously threatened by an increase in atmospheric carbon dioxide (CO 2 ) concentrations. To support sustainable development in the 21st century, controlling the global warming caused by the increasing atmospheric CO 2 levels has become a main scientific and technological challenge. 1 To prevent catastrophic events related to atmospheric CO 2 , the emission of CO 2 should be reduced as soon as possible. One of the most promising solutions to overcome this challenge is the conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Previous research has demonstrated that hydrogen can be produced from water in supercritical-water up-gradation of organic waste, such as polyethylene (PE) and sulfur-containing rubber, If the hydrogen produced during the hydrothermal cracking of polymer wastes could be directly used to reduce CO 2 , then an efficient process for CO 2 conversion and polymer waste utilization would be realized. Thus, we studied the poetential of the reduction of CO 2 under hydrothermal conditions in the presence of organic waste …”
Section: Reduction Of Co2 In the Presence Of Organic Wastementioning
confidence: 99%
“…Previous research has demonstrated that hydrogen can be produced from water in supercritical-water up-gradation of organic waste, such as polyethylene (PE) and sulfur-containing rubber, If the hydrogen produced during the hydrothermal cracking of polymer wastes could be directly used to reduce CO 2 , then an efficient process for CO 2 conversion and polymer waste utilization would be realized. Thus, we studied the poetential of the reduction of CO 2 under hydrothermal conditions in the presence of organic waste …”
Section: Reduction Of Co2 In the Presence Of Organic Wastementioning
confidence: 99%
“…In particular, biomass residues, glycerin [50] or residues of Sulphur-containin polymers have been used to reduce the metal and reutilize it in the process [56]. Additionally, some authors have proved that CO 2 reduction can be carried out in hydrothermal media by oxidation of an alcohol, without addition of any metals [57].…”
Section: Hydrothermal Co 2 Reductionmentioning
confidence: 99%
“…However, these technologies still face important limitations, especially with respect to the selectivity and the productivity of the conversion reaction, and new investigations regarding process intensification and energy integration are needed to make these technologies technically and economically feasible [6] Among the different carbon dioxide conversion technologies, the hydrothermal reduction of CO 2 stands out since it has already shown the potential to selectively convert carbon dioxide into valuable products such as formic acid, methane and methanol, favored by the increased reactivity of CO 2 in hydrothermal conditions [7][8][9][10]. In this process, gaseous CO 2 , or CO 2 captured in a basic aqueous solution as bicarbonate, is reduced using zero-valent metals [10][11][12] or organics [11,[13][14][15] as reductants, eliminating in this way the need of using hydrogen gas with all its economical and safety issues. In many of these processes water acts not only as a solvent but also as a hydrogen source, and, what it is more, the reduction performed with the hydrogen so generated is faster than the reaction using gaseous hydrogen [11,16].…”
Section: Introductionmentioning
confidence: 99%